Nitrous Oxide Cycling in the Fram Strait - Arévalo-Martínez, Damian L.; Löscher, Carolin R.; Brown, Ian J.; Rees, Andrew P.; Kitidis, Vassilis; Bange, Hermann W. (2019)
The Arctic Ocean is particularly sensitive to climate change. Its ecosystem structure and function are prone to be disturbed (among others) by fast warming and massive retreat of sea-ice, which in turn, might result in feedbacks on climate. As the third most important greenhouse gas and major ozone-depleting substance in the stratosphere, nitrous oxide (N2O) is a crucial parameter to study in order to monitor ocean’s state and its role in the production and exchange of climate-relevant substances to the atmosphere. Although studies have suggested potential N2O sinks in subpolar-polar waters, little is known about their relevance for regional and global budgets. In this presentation, we show the first results of a study carried out in summer 2018, during which we conducted extensive measurements of N2O at the sea surface and the water column in the Fram Strait between Svalbard and Greenland. We also conducted a detailed survey of functional gene markers of nitrogen cycling and performed incubation experiments for biological nitrogen fixation. Using the combined data set we: provide the first estimate of sea-to-air transfer of N2O in the region, show the contrasting depth distribution between east and -western sides of the Strait, and discuss the dynamic balance between water mass transport, solubility effects and production/consumption. Considering the connectivity between the Strait and the subpolar North Atlantic (through the East Greenland Current), this study represents an important contribution to the understanding of the biogeochemistry of the region and it allows assessing expected changes with further decline in Arctic sea-ice.